Physicochemical, Biochemical and Genotoxic Profile of Subchronic Exposure of Wister Rats to Treated Crude Oil Exploration Water (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Crude oil exploration water is the major waste product generated from petroleum exploration and production activities and is known to be a complex composition of numerous hazardous chemicals, including large quantities of heavy metals, inorganic, and organic substances and naturally occurring radioactive materials (NORMs).Objectives:This study was designed to investigate the physicochemical, biochemical and genotoxic profile of subchronic exposure of Wister rats to treated crude oil exploration water (TCOEW).Materials and Methods: Fifty rats were randomly assigned to five treatment groups, with ten rats per group, and treated with five concentrations (1%, 5%, 10% and 20%) of TCOEW. Each TCOEW concentration was administered for 90 days ad-libitum as normal drinking water to each group, while the control group was given tap water. Blood, liver, kidney, thymus, spleen and femoral bone of the animals were collected at the end of exposure for biochemical and histological assessments. The pH, conductivity, and turbidity were carried out on-site, while other physicochemical parameters were determined using standard laboratory methods. Data were analysed using descriptive statistics and ANOVA at α 0.05.Results:Treated crude oil exploration water caused a significant (p < 0.05) increase in RBC, PCV and Hb while other hematological and biochemical parameters showed no difference. Also, TCOEW cause a significant increase in polychromatic erythrocytes (PCEs) in genotoxicity test and no major lesion were seen in the histopathology studies. Treated Crude Oil Exploration Water does not comply with FEPA standards of produced water due to high conductivity, salinity and total dissolved solid of the sample. The marked increase in micronuclei polychromatic erythrocyte formation (MNPCE) showed that TCOEW might be genotoxic and this could be responsible for the significant increase RBC, parked cell volume (PCV) and hemoglobin (Hb) observed.Conclusion: Although TCOEW does not totally meet FEPA standard for effluent discharge, it has mild genotoxic effect.
Keywords: Physicochemical and genotoxic; Effluents treated crude oil exploration water; Flame Atomic Absorption Spectrometry